2017
DOI: 10.1007/978-3-319-43394-3_25
|View full text |Cite
|
Sign up to set email alerts
|

Soil Contamination and Human Health: A Major Challenge for Global Soil Security

Abstract: This chapter aimed to demonstrate, by several illustrated examples, that Human Health should be considered as another major challenge of global soil security by emphasizing the fact that (a) soil contamination is a worldwide issue, estimations can be done based on local contamination but the extent and content of diffuse contamination is largely unknown; (b) although soil is able to store, filter and reduce contamination, it can also transform and make accessible soil contaminants and their metabolites, contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…14 Once the soil is contaminated, the people of the land are not entirely free from the contamination. 15,16 This explains the reason why another study in the same region found toxic metals (lead, cadmium and mercury) in the breast milk of nursing mothers. 17 This calls for urgent environmental protection policies in that particular region.…”
Section: Soil and Water As Health Risk Factorsmentioning
confidence: 97%
“…14 Once the soil is contaminated, the people of the land are not entirely free from the contamination. 15,16 This explains the reason why another study in the same region found toxic metals (lead, cadmium and mercury) in the breast milk of nursing mothers. 17 This calls for urgent environmental protection policies in that particular region.…”
Section: Soil and Water As Health Risk Factorsmentioning
confidence: 97%
“…In a field simulation experiment, Zheng et al [56] reported that these acid dispositions decreased soil respiration by 0.23%, which were further exacerbated up to 1.54%, while both acid and N deposition occurred in soil. As discussed in Sections 2 and 3, the contamination of soils by pollutants and their transport, diffusion, and persistence in soils are affected by physical, chemical and biological properties and processes [57] (Scheme 1). In the following sections, we will expound linkages among climate change drivers, soil processes, and the exposure of chemical pollutants from empirical and predictive research perspective.…”
Section: Changing Environments-climate Change and The Soil Propertiesmentioning
confidence: 99%
“…Batteries in many electronic devices should be managed as hazardous waste because of their toxic contents or reactive properties [ 5 ]. In this context, green electronics technology provides solutions that are well suited to the broad needs of an energy-efficient society.…”
Section: Introductionmentioning
confidence: 99%